New Insights Into the Activity of Apple Dihydrochalcone Phloretin: Disturbance of Auxin Homeostasis as Physiological Basis of Phloretin Phytotoxic Action - Smailagić﻿﻿﻿, Dijana; Banjac, Nevena; Ninković﻿﻿﻿, Slavica; Savić﻿﻿﻿, Jelena; Ćosić﻿﻿﻿, Tatjana; Pěnčík, Aleš; Ćalić﻿﻿﻿, Dušica; Bogdanović﻿﻿﻿, Milica; Trajković﻿﻿﻿, Milena; Stanišić, Mariana (Frontiers in Plant Science, 2022)
Apple species are the unique naturally rich source of dihydrochalcones, phenolic compounds with an elusive role in planta, but suggested auto-allelochemical features related to “apple replant disease” (ARD). Our aim was to elucidate the physiological basis of the phytotoxic action of dihydrochalcone phloretin in the model plant Arabidopsis and to promote phloretin as a new prospective eco-friendly phytotoxic compound. Phloretin treatment induced a significant dose-dependent growth retardation and severe morphological abnormalities and agravitropic behavior in Arabidopsis seedlings. Histological examination revealed a reduced starch content in the columella cells and a serious disturbance in root architecture, which resulted in the reduction in length of meristematic and elongation zones. Significantly disturbed auxin metabolome profile in roots with a particularly increased content of IAA accumulated in the lateral parts of the root apex, accompanied by changes in the expression of auxin biosynthetic and transport genes, especially PIN1, PIN3, PIN7, and ABCB1, indicates the role of auxin in physiological basis of phloretin-induced growth retardation. The results reveal a disturbance of auxin homeostasis as the main mechanism of phytotoxic action of phloretin. This mechanism makes phloretin a prospective candidate for an eco-friendly bioherbicide and paves the way for further research of phloretin role in ARD.